The Performing Text: Laurence Sterne's The Life and Opinions of Tristram Shandy , Gentleman and the Theatrical Paradox - Dick, John Alexander (My University, 1994)
This thesis examines the influence of the' eighteenth-century theatre on the composition and structure of Laurence Sterne's Tristram Shandy. Eighteenth-century theatre epitomises the paradoxical drive toward a stable model of experience in texts and the simultaneous breakdown of textual stability in performance. Sterne was familiar with his contemporary theatre and makes numerous references to it throughout Tristram Shandy; this theatrical paradox of text and performance represents a significant mode of inquiry into the problems and paradoxes of social communication and literary signification addressed in the novel.
Each chapter explores one aspect of the eighteenth-century theatre and its appearance in major episodes in Tristram Shandy. Sterne's use of theatrical techniques is compared with the similar investigations of other eighteenth-century writers, including Dryden, Addition, Hogarth, and Garrick -- who appear in the novel -- as well as Fielding, Diderot, Shaftesbury, and Richardson. Chapter one discusses the intimate and often antagonistic relationship of theatre performers and writers and their audience and its similarity to Tristram's constructed relationship with his audience. Chapter two examines pictorial modes of signification - naturalistic gesture and tablleaux -- in the theatre. These techniques obviously influenced Sterne's sense of visual detail in the novel, but the inherent textuality of his medium allows him to expose the textual nature of this attempt to transcend verbal declamation. Chapter three deals with the similar issue of theatrical dialogue. While dialogue in performance suggests the interweaving presence of multiple discourses, Sterne suggests that this play of alternatives tends to be subsumed within a desire for a single dominating or incontestable point of view.
Keywords: English Language and Literature; English Language and Literature